In situ immobilization of lysine decarboxylase on a biopolymer by fusion with phasin: Immobilization of CadA on intracellular PHA. Issue 10 (October 2016) - Seo, Hyung-Min; Kim, Jung-Ho; Jeon, Jong-Min; Song, Hun-Suk; Bhatia, Shashi Kant; Sathiyanarayanan, Ganesan; Park, Kyungmoon; Kim, Kwang Jin; Lee, Sang Hyun; Kim, Hyung Joo; Yang, Yung-Hun
Graphical abstract: Highlights: An in situ immobilization system for enzymatic cadaverine production was developed. CadA was immobilized on poly (3-hydroxybutyrate) (P(3HB)) biopolymer granules. Increased P(3HB) production was observed with phasin-fused CadA. The thermal stability increased with immobilization. Repetitive reactions of the CadA–P(3HB) complex were observed. Abstract: Cadaverine is a useful chemical that can be produced by lysine decarboxylase up to molar concentration levels. To develop a convenient and reusable production process, we performed intracellular immobilization of lysine decarboxylase (CadA) using poly(3-hydroxybutyrate) (P(3HB)) and PhaP1 (P(3HB) granule-associated protein) from Ralstonia eutropha . By adding 591 bp of the entire phaP1 gene sequence to the 3′ end of the cadA gene, CadA was successfully fused to PhaP1. The phasin-fused CadA bound to the intracellular P(3HB) granules, which enabled the reuse of CadA in repetitive enzyme reactions. Although immobilization of the CadA–P(3HB) complex was not effective over extended temperature and pH ranges, the immobilized CadA exhibited increased thermal stability, with a half-life of 70 h at 50 °C. The CadA–P(3HB) complex achieved a 75–80% conversion yield over five reaction cycles without laborious immobilization steps. This study indicates the feasibility of in situ immobilization of lysine decarboxylase by phasin fusion.